CFN lectures on functional nanostructures. - Röthig, Christian; Schön, Gerd; Vojta, Matthias (Lecture notes in physics, 2011)
This series of books contains selected and edited lectures from summer schools organized by the Center for Functional nanostructures (CFN) at the University of Karlsruhe. The mission of the CFN is to carry out research in the following areas: nanophotonics, nanoelectronics, molecular nanostructures and nanostructured materials. The aim of the summer schools is mainly to exchange new ideas and illustrate emerging research methodologies through a series of topical, introductory lectures. This is reflected by both the selection of topics addressed in the present volume, nanoelectronics, as well as the tutorial aspect of the contributions.